Penerapan aritmatika modulo untuk menguji validitas dan mengembangkan nomor ISBN (International Standard Book Number) - Lukman Ibrahim; Syamsul Bahri; Irwansyah - (University of Mataram, 2018)
International Standard Book Number or ISBN is a code that contains information about the title, the publisher, the different types of materials for making the book, and publisher group from a book. The ISBN code of a book along with its development need to be checked for validity, because the more books are published, the more chance the book will be copied so that it has a double ISBN number. This research show that the use of modulo arithmetic in arranging ISBN for a book, especially ISBN-10 and ISBN-13. In this research too discussed about validation ISBN-10 and ISBN-13 using modulo arithmetic and expanded by developing an ISBN-n, for a natural number n greater than 10. Validation will be carried out in two stages, namely manually using modulo arithmetic calculation and then computing, by compiling java-based application to validate an ISBN. The development of ISBN-n for n ∊ ℕ and n ≥ 11 use the advantages of ISBN-10 and ISBN-13 and (Memorandum of Understanding/MoU) ISBN agency. Case studies in the Department of Library and Archives of West Nusa Tenggara Province on the ISBN validity of additional collection books for the 2015-2016 period showed that the ISBN validity of these books is 96%.